Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1603/me09252
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Larval Competition Between Invasive Aedes japonicus and Native Aedes triseriatus (Diptera: Culicidae) and Adult Longevity

Abstract: The Asian rock pool mosquito Aedes japonicus (Theobald) inhabits natural and artificial container habitats, some of which are occupied by the native treehole mosquitoAedes triseriatus (Say), a vector of LaCrosse encephalitis virus. A laboratory experiment was used to evaluate the effects of nutrient limitation and interspecific interactions between these species. The goal was to address two related hypotheses. First, interspecific interactions between these species show competitive asymmetry with the invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…The third hypothesis, therefore, concerned the competitive disadvantage of the native species in the presence of a second invasive is supported by a small number of studies indicating A. triseriatus as an inferior larval competitor to A. japonicus (Andreadis and Wolfe 2010;Alto 2011). Our study found A. japonicus wellestablished in northern New Jersey, where A. triseriatus counts were depressed compared to the rest of the state in the 2002 baseline.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The third hypothesis, therefore, concerned the competitive disadvantage of the native species in the presence of a second invasive is supported by a small number of studies indicating A. triseriatus as an inferior larval competitor to A. japonicus (Andreadis and Wolfe 2010;Alto 2011). Our study found A. japonicus wellestablished in northern New Jersey, where A. triseriatus counts were depressed compared to the rest of the state in the 2002 baseline.…”
Section: Discussionsupporting
confidence: 58%
“…(1) A. albopictus is a stronger larval competitor and would displace the native A. triseriatus with some exceptions, see hypothesis #3 (Livdahl and Willey 1991;Novak et al 1993;Teng and Apperson 2000;Lounibos et al 2001); (2) A. japonicus is an inferior larval competitor to A. albopictus and a superior larval competitor to A. triseriatus (Armistead et al 2008;Andreadis and Wolfe 2010;Alto 2011) resulting in similarly detectable trends in the adult populations; (3) A. triseriatus displacement trends are context-dependent with urban areas experiencing sharper declines compared to less disturbed rural environments Willey 1991, Lounibos et al 2001); (4) interactions among these species will be dependent on climatic conditions, with warmer temperatures generally favoring larval A. albopictus (Hanson and Craig 1995;Teng and Apperson 2000;Armistead et al 2008), translating into increased adult population growth for this species.…”
Section: Introductionmentioning
confidence: 99%
“…Resource competition within the larval habitat has an important role in shaping community structure and can influence both epidemiologically important adult life history traits, and the geographic distribution of mosquito species , Reiskind and Lounibos 2009, Alto 2011. The objective of this experiment was to determine the effect of interspecific competition and intraspecific competition intensity on larval Ae.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus develop, allochthonous inputs in the form of plant and animal detritus are the primary energy source (Yee andJuliano 2006, Kesavaraju et al 2007). The ratio and types of detritus sources within the larval habitat significantly influence mosquito population growth, interspecific competition, and the capacity of mosquito populations to vector pathogens (Alto et al 2005, Murrell and Juliano 2008, Alto 2011. Therefore, understanding how different detritus types influence larval development, and interspecific interactions has many important implications for human health and arbovirus epidemiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation